Totally tubeless percutaneous nephrolithotomy: one year single institute prospective study - Bhangu, G. S.; Bansal, Darpan; Shah, Avreen Singh; Vyas, Nachiketa; Priyadarshi, Shivam; Sharma, K. K. (International Surgery Journal, 2016)
Background:Urolithiasis forms an important domain in the practice of urology. PCNL is an important armamentarium in the management of urolithiasis, especially for larger and complex stones. The objective of this study was to study the safety and feasibility of totally tubeless (tubeless and stentless) percutaneous nephrolithotomy in selected cases. Methods: The study consisted of 50 cases operated between June 2011 - May 2012 in Department of urology, SMS medical college and hospital, Jaipur. Patients were taken for standard fluoroscopy guided PCNL in prone position with track dilatation up to 24hours. Decision to go for totally tubeless procedure was taken intra-operatively. No weightage was given to the puncture (supra or infra costal) and the calyx selected for access. The exclusion factors were significant intraoperative bleeding, more than one track, residual stones, and injury to pelvicalyceal system. The parameters studied were hospital stay, post-operative pain, analgesia requirements and complication rates. Results:Totally tubeless PCNL constituted 6.2% of the total PCNL during this period. The age ranged from 20 - 70 years with a mean of 43years. Average stone burden was 26.8mm. Mean hospital stay was 1.5 days with 60% of being discharged after 24 hours. Post-operative analgesia was required in 60% and 28% of the patients, with moderate to severe pain on day0 and 1 respectively. No patient required intraoperative blood transfusion. Three patients had mild haematuria on day 0, with one requiring blood transfusion on day 2. No patient developed urinary leakage from skin wound. One patient developed urinoma requiring DJ stenting. No readmission was reported in 1 month follow up. Conclusions:this study demonstrated that totally tubeless PCNL is safe well tolerated procedure, not affected by access track. It significantly decreases post-operative pain, analgesia requirement and hospital stay. The only limitation being its applicability in highly selected cases.